1990
DOI: 10.1113/jphysiol.1990.sp018160
|View full text |Cite
|
Sign up to set email alerts
|

Rapid co‐transport of sodium and chloride ions in giant salivary gland cells of the leech Haementeria ghilianii.

Abstract: SUMMARY1. Double-barrelled Cl--selective microelectrodes were used to measure the apparent intracellular Cl-activity (a',) and membrane potential (Em) of leech salivary gland cells. In standard physiological solution buffered with HEPES (10 mM), intracellular Cl-activity (corrected for interference) was 38 + 8 mm (n = 11) compared to a value of 12-8 mm expected for passive Cl-distribution. The mean Em was -49*4+ 8-2 mV (n = 21) which was about 27 mV negative to the Clequilibrium potential.2. Removal of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The cellular mechanisms of salivary-gland secretion have been well investigated using the salivary gland of the giant leech Haementeria ghilianii (Walz et al 1988). Wuttke and colleagues investigated the cotransport of Na + and Cl -and found that Cl -uptake is sodium-dependent and Cl -accumulates in the cells even against an electrochemical gradient (Wuttke and Berry 1990). They also analyzed pH regulation and its effects on salivary-gland secretion (Wuttke et al 1994).…”
Section: Function Of the Crop And Intestinementioning
confidence: 97%
“…The cellular mechanisms of salivary-gland secretion have been well investigated using the salivary gland of the giant leech Haementeria ghilianii (Walz et al 1988). Wuttke and colleagues investigated the cotransport of Na + and Cl -and found that Cl -uptake is sodium-dependent and Cl -accumulates in the cells even against an electrochemical gradient (Wuttke and Berry 1990). They also analyzed pH regulation and its effects on salivary-gland secretion (Wuttke et al 1994).…”
Section: Function Of the Crop And Intestinementioning
confidence: 97%